2020
DOI: 10.1002/cbin.11533
|View full text |Cite
|
Sign up to set email alerts
|

X‐box binding protein 1 (XBP1) function in diseases

Abstract: The accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER) causes endoplasmic reticulum stress (ERS), which is characteristic of cells with high levels of secretory activity and is involved in a variety of diseases. In response to ERS, cells initiate an adaptive process named the unfolding protein response (UPR) to maintain intracellular homeostasis and survival. However, long term and unresolved ERS can also induce apoptosis. As the most conserved signaling branch of UPR, the IRE1-XB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Xbp-1 is a downstream transcription factor stimulated by ER stress that is spliced by activated IRE1 α [ 50 , 51 ]. Increased spliced Xbp-1 (sXbp-1) reverses HG-induced reactive oxygen species production and extracellular matrix expression [ 29 ].…”
Section: Mechanism Of Er Stress In Dnmentioning
confidence: 99%
“…Xbp-1 is a downstream transcription factor stimulated by ER stress that is spliced by activated IRE1 α [ 50 , 51 ]. Increased spliced Xbp-1 (sXbp-1) reverses HG-induced reactive oxygen species production and extracellular matrix expression [ 29 ].…”
Section: Mechanism Of Er Stress In Dnmentioning
confidence: 99%
“…In this study, we first identified the endoplasmic reticulum (ER) stress effector Xbp1 as a common TF for HO bulk-RNA-seq, HO scRNA-seq, and the integrated scRNA data (including GSE168153, GSE138515, and GSE102929 datasets under simulated HO pathological conditions) using a comprehensive network analysis combined with a modified SCENIC approach. XBP1 was found to be an important regulatory pathway for the unfolding protein response that occurred in response to ER stress and played an important role in both physiological and pathological conditions, and its activity had a significant effect on the progression and prognosis of numerous diseases [ 104 ]. In this study, 160 genes were identified as core downstream regulatory targets of XBP1, with significant interactions among them, and they mainly played important roles in the Golgi vesicle transport, ER protein processing, cellular communication, and translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The luminal domain of IRE1 dissociates from GRP78 under ER stress conditions, which causes the phosphorylation and dimerization of IRE1, which activates endoribonuclease and forms mature XBP1. Mature XBP1 regulates ERAD, ER chaperones, and the protein transport and lipid synthesis processes to maintain homeostasis in the ER environment [ 160 , 161 ]. PERK is the main protein that is responsible for the attenuation of mRNA translation under ER stress conditions and prevents newly synthesized proteins from entering the ER lumen.…”
Section: Mechanisms In Anticancer Actions Of Bioactive Compoundsmentioning
confidence: 99%